Heterologous versus homologous COVID-19 booster vaccination in previous recipients of two doses of CoronaVac COVID-19 vaccine in Brazil (RHH-001): a phase 4, non-inferiority, single blind, randomised study - Costa Clemens, SA; Weckx, L; Clemens, R; Almeida Mendes, AV; Ramos Souza, A; Silveira, MBV; da Guarda, SNF; de Nobrega, MM; de Moraes Pinto, MI; Gonzalez, IGS; Salvador, N; Franco, MM; et al. (Elsevier, 2022)
Introduction The inactivated whole-virion SARS-CoV-2 vaccine (CoronaVac, Sinovac) has been widely used in a two-dose schedule. We assessed whether a third dose of the homologous or a different vaccine could boost immune responses.